Using Causal Loop Diagrams to Conceptualize Groundwater as a Social-Ecological System - Bouchet, Louis; Thoms, Martin C.; Parsons, Melissa (Frontiers in Environmental Science, 2022)
Groundwater systems are social-ecological systems (SES) in which human communities, Groundwater Dependent Ecosystems (GDE) and groundwater resources are linked, and therefore cannot be studied in isolation. Complex adaptive systems are characterised by non-linear relationships and feedbacks between the system variables. Modeling feedbacks between social and ecological variables of groundwater systems requires a shift from traditional hydrogeological studies to more holistic approaches that simulate groundwater as a SES. A framework was developed to study and manage groundwater as a social-ecological system. Operationalizing the framework to develop empirical models that consider the social and ecological aspects of groundwater dynamics requires translating the framework components into measurable model inputs that capture the key relationships between social and ecological components. Causal loop diagrams (CLD) are an ideal tool for translating between a conceptual framework and an operational, empirical model. Causal loop diagrams can reveal system complexity associated with the interaction of social, ecological and hydrological components, and identify key inputs that need to be considered to model groundwater as a SES. This paper applies CLD to conceptualize the feedbacks between the social, ecological and hydrological components of a groundwater system. The concept is applied to the groundwater system in the island of Nauru, and shows that two balancing feedbacks help maintain the system in a precarious state of usability while several reinforcing feedbacks in the social subsystem apply constant pressure to the system. The CLD reveals that the social subsystem is large and complex, even though the island population is small (approximately 10,000 people). It also demonstrates that the social system is by far the larger disruptor and has the greater potential to alter system states.